The constitutional and conventional problems of the application of the sentence of the acquit in the process by reason of the public function - Núñez Pérez, Fernando Vicente (2024)
The most controversial institution incorporated into the Criminal Procedure Code of 2004 was the sentence of the acquitted, which is the power that the Superior Criminal Chamber has, when resolving the appeal that may have been filed against a previous acquittal sentence issued in favor of the accused (first instance), in being able to amend it in a conviction against this same procedural subject (second instance), sentencing decision that originally could only be questioned by means of the appeal of cassation. However, the national legislator, through Law No. 31592 of October 26th 2022, has decided to briefly reform this adjective norm, where the legal novelty is that this convicted person has the possibility of challenging his sentence via a new appeal, in which the Criminal Chamber of the Supreme Court is enabled to act as a judicial instance, this according to the exclusive rules of the common criminal process (base process). However this legal modification has omitted to refer to the special rules of the process due to the public function (special process), a process in which the defendant is an appraiser, affecting with this legal gap the plurality of instance, the double conforming and the comprehensive review, an aspect that has been totally unnoticed by the specialized doctrine and national jurisprudence. Thus, a series of recommendations are proposed that are addressed to each of these four sub-processes and revolve around the need to enable the possibility of challenge via appeal by the person convicted for the first time in the second instance, also establishing the jurisdiction respective to the corresponding Supreme Criminal Chamber; therefore, if these modifications do not occur, the previously acquitted person cannot be convicted in the second instance.